MATEC Web of Conferences - Zhdanova, A. O. specialist in the field of power engineering engineer of Tomsk Polytechnic University 1989- (EDP Sciences, 2018)
The danger of forest fires and their large-scale consequences is facing humanity more and more sharply from year to year. We carried out experimental studies to determine the thermal characteristics (thermal conductivity, heat capacity, thermal diffusivity) and thermokinetic characteristics (activation energy, pre-exponential factor) of typical forest combustible materials and their mixtures for a wide range of temperatures (298-423 K). A generalization of experiments for typical forest combustible materials of the Far Eastern Federal District of Russia was performed. The established experimental values can be used for mathematical modeling of occurrence, propagation and extinguishing of forest fires.